UI-Design Driven Model-Based Testing - Bowen, Judy; Reeves, Steve (Electronic Communications of the EASST, 2010)
Testing interactive systems is notoriously difficult. Not only do we need to ensure that the functionality of the developed system is correct with respect to the requirements and specifications, we also need to ensure that the user interface to the system is correct (enables a user to access the functionality correctly) and is usable. These different requirements of interactive system testing are not easily combined within a single testing strategy. We investigate the use of models of interactive systems, which have been derived from design artefacts, as the basis for generating tests for an implemented system. We give a model-based method for testing interactive systems which has low overhead in terms of the models required and which enables testing of UI and system functionality from the perspective of user interaction.